M33 Long-term efficacy of nintedanib is maintained in patients with idiopathic pulmonary fibrosis (ipf) irrespective of dose: subgroup analysis of inpulsis-on. (15th November 2017) - Crestani, B; Kolb, M; Wallaert, B; Quaresma, M; Stansen, W; Richeldi, L
Abstract : Introduction and Aim: In the INPULSIS trials, nintedanib reduced the annual rate of decline in FVC versus placebo in patients with IPF (−113.6 versus −223.5 mL/year). Patients completing the 52 week treatment period could receive open-label nintedanib in an extension trial (INPULSIS-ON). Patients receiving nintedanib or placebo 150 mg bid at the end of INPULSIS received nintedanib 150 mg bid in INPULSIS-ON; patients receiving nintedanib or placebo 100 mg bid at the end of INPULSIS received nintedanib 100 mg bid or 150 mg bid in INPULSIS-ON, based on patient/investigator discussions. Dose reduction from 150 mg bid to 100 mg bid was allowed to manage adverse events; re-escalation to 150 mg bid was permitted. Our objective was to assess whether dose influenced the effect of nintedanib on FVC decline in INPULSIS-ON. Methods: The annual rate of decline in FVC over 96 weeks in INPULSIS-ON was assessed in subgroups of patients by whether they were treated with nintedanib 150 mg bid only, 100 mg bid only, or both 150 mg bid and 100 mg bid. All available FVC measurements collected at time points between baseline and week 96 were used to calculate FVC decline. These analyses were descriptive and based on a data snapshot in October 2015. Results: A total of 734 patients received nintedanib in INPULSIS-ON: 436 patients (59.4%) received nintedanib 150 mg bid, 53 patients (7.2%) received nintedanib 100 mg bid, and 245 patients (33.4%) received both doses. The annual rates of decline in FVC over 96 weeks were −116.4 (8.9) mL/year, −79.0 (30.1) mL/year, and −126.2 (11.4) mL/year in patients treated with nintedanib 150 mg bid, 100 mg bid, or both doses, respectively, and were consistent with the annual rate of decline in FVC over 96 weeks in all patients treated with nintedanib (−117.8 [6.8] mL/year). Conclusion: Data from INPULSIS-ON demonstrated that the annual rate of decline in FVC was similar in patients treated with nintedanib 150 mg bid, 100 mg bid, or both doses. The long-term efficacy of nintedanib in reducing disease progression was maintained in patients with IPF who required dose adjustments to manage adverse events. Please refer to page A262 for declarations of interest in relation to abstract M33.